Master Education and Academic Career Track in Russia - A. V. Garmonova; E. A. Opfer; D. V. Shcheglova (Высшее образование в России)
The master’s degree is an obligatory stage for those who are planning to enter PhD. That is why it should have a clear academic track. Embedding the master’s degree in the academic track allows universities to sum up their efforts to support young scientists. There is an urgent need to support scientific centers in Russian universities. When the universities are competing for academic leadership, academic tracks become the ground for the development strategies.Previous researches showed that most students were ready to choose an academic track when they were master’s students. Thus, the academic track starts long before entering the doctoral programs. The study results reveal that master’s students do not have an opportunity to build an individual academic track within “hybrid” master’s programs. The Russian master’s degree programs shortly involve young researchers in projects, and this applies to all types of universities, including the research ones. The structure and ways of involving students in science do not differ in undergraduate and postgraduate programs. Master’s students who choose academic track do it without changing the major program. However, this trend doesn’t cover all the students. Master’s students use academic tracks to upgrade their professional skills for the further career but not at university or scientific institution.